INFLUENCE OF STORAGE CONDITIONS ON FREEZE-DRIED APPLE FORTIFIED WITH VITAMIN E - CORTÉS R., Misael; CHIRALT B., Amparo; SUAREZ M., Héctor (Vitae, 2009)
The effect of different storage conditions (temperature: 4, 20 and 30 °C; time: 30, 60, 90 and 180 days; package: with and without vacuum), is evaluated in terms of the stability of vitamin E, color and texture of freeze-dried apple fortified with vitamin E, using matrix engineering as a methodology for obtaining functional foods. The vitamin’s quantification was carried out using gas chromatography. The color’s by coordinates CIE- L*a*b*, hue and chroma and texture by penetration test. Degradation of vitamin E was modeled using a first order kinetics. However the kinetic constants weren’t fitted by Arrhenius equation, due to an abrupt change in them between 4 and 20ºC, the effect of the transition from glassy to rubbery state in the product. At 4ºC, the color was acceptable at 180 days, whereas browning is observed at 20ºC and 30ºC, and is higher according to temperature and time. Vacuum packaging showed a negative effect in the samples color, probably due to the mechanical effects. Textural changes, caused by progressive moisture gain, are related to permeability of packaging material, generating loss of crunch, which was well evaluated at the initial control time (30 day).